2016
DOI: 10.1515/eje-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Guided by the light: Roost choice and behaviour of urban Rainbow Lorikeets (Trichoglossus haematodus)

Abstract: 1. The formation of large communal roosts is a conspicuous phenomenon associated with a wide range of bird species successfully exploiting urban environments. In many Australian cities, the abundance of the Rainbow Lorikeet (Trichoglossus haematodus), a native parrot, has increased markedly in recent decades, with the species roosting in very large numbers within suburban sites. These roosting locations are noisy and cause significant fouling of the land beneath, resulting in conflict with humans. 2. We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Changing or reducing artificial light can discourage birds from settling in areas where they pose a danger or nuisance to humans. For example, three studies in our map showed how artificial light levels can influence roost site selection for nuisance species in urban environments [119][120][121]. Another study changed the colour of runway lighting to reduce insect attraction, thereby reducing the number of birds on the runway [122].…”
Section: What Evidence Exists On Continuous Artificial Illumination C...mentioning
confidence: 98%
“…Changing or reducing artificial light can discourage birds from settling in areas where they pose a danger or nuisance to humans. For example, three studies in our map showed how artificial light levels can influence roost site selection for nuisance species in urban environments [119][120][121]. Another study changed the colour of runway lighting to reduce insect attraction, thereby reducing the number of birds on the runway [122].…”
Section: What Evidence Exists On Continuous Artificial Illumination C...mentioning
confidence: 98%
“…In addition to facilitating range expansions, urbanization is altering the abundance of cavity nesters. Species such as the rainbow lorikeet, are well adapted to make use of nectar resources available in many planted urban plants and trees, has increased in abundance following the expansion of urban areas along the east coast and is invasive in cities in Western Australia and Tasmania where it is introduced (Shukuroglou & McCarthy, 2006;Koch et al, 2008;Daoud-opit & Jones, 2016). However, the addition of many novel species to urban cavity breeding assemblages remains little understood.…”
Section: Urban Environments In Australiamentioning
confidence: 99%